Fam20C in Human Diseases: Emerging Biological Functions and Therapeutic Implications - Xu, Rongsheng; Tan, Huidan; Zhang, Jiahui; Yuan, Zhaoxin; Xie, Qiang; Zhang, Lan (Frontiers in Molecular Biosciences, 2021)
Fam20C, a typical member of Fam20 family, has been well-known as a Golgi casein kinase, which is closely associated with Raine Syndrome (RS). It can phosphorylate many secreted proteins and multiple substrates; and thereby playing a crucial role in biological functions. More importantly, Fam20C has been also found to enhance the metastasis of several types of human cancers, such as breast cancer, indicating that Fam20C may be a promising therapeutic target. Accordingly, some small-molecule inhibitors of Fam20C have been reported in cancer. Taken together, these inspiring findings would shed new light on exploiting Fam20C as a potential therapeutic target and inhibiting Fam20C with small-molecule compounds would provide a clue on discovery of more candidate small-molecule drugs for fighting with human diseases.